UJI EFEKTIVITAS EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) SEBAGAI REPELLENT NABATI DALAM MENGURANGI JUMLAH LALAT SELAMA PROSES PENJEMURAN IKAN ASIN - Dewi Utari (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
The implementation of food sanitation aims to eliminate the risk of contamination by microorganisms at different stages in the production and processing of food. House fly (Musca domestical) can act as a vector of tyfus disease, other stomach ailments such as dysentery and diarrhea, cholera, and skin diseases. Salt fish processing business is the largest part of traditional fish processing business especially in Senamabah Village, Muara Bengkal Sub-district, East Kutai Regency. Problems that arise from the traditional processing of salted fish with sun drying, have the weakness of one of the fly flies that can damage salted fish products especially during the rainy season. This research is a quasi-experimental research (Quasi Experiment Design). Field research is difficult to carry out randomization. For field research, usually using a quasi-experiment, this study used a Completely Randomized Design (RAL), consisting of 3 treatments with 1 control and 3 repetitions on each treatment. This research is about the effectivity test of pandan wangi leaf extract (Pandanus amaryllifolius Roxb) as Refellent Vegetable in Reducing Number of Flies during the drying process of Salted Fish, concentration 5% after 30, 60 and 90 minutes observation with the average percentage of moisture by 25% decline 55%, concentration 10% after 30, 60 and 90 minutes observation with the average percentage of up to 13% with 77% repulsion and 15% concentration after 30, 60 and 90 minutes observation with percentage of average 6% with 90% resistance.